ZEB2 mediates multiple pathways regulating cell proliferation, migration, invasion, and apoptosis in glioma. - Songtao Qi (Public Library of Science (PLoS), 2012)
Background The aim of the present study was to analyze the expression of Zinc finger E-box Binding homeobox 2 (ZEB2) in glioma and to explore the molecular mechanisms of ZEB2 that regulate cell proliferation, migration, invasion, and apoptosis. Methodology/principal findings Expression of ZEB2 in 90 clinicopathologically characterized glioma patients was analyzed by immunohistochemistry. Furthermore, siRNA targeting ZEB2 was transfected into U251 and U87 glioma cell lines in vitro and proliferation, migration, invasion, and apoptosis were examined separately by MTT assay, Transwell chamber assay, flow cytometry, and western blot. Results The expression level of ZEB2 protein was significantly increased in glioma tissues compared to normal brain tissues (P<0.001). In addition, high levels of ZEB2 protein were positively correlated with pathology grade classification (P = 0.024) of glioma patients. Knockdown of ZEB2 by siRNA suppressed cell proliferation, migration and invasion, as well as induced cell apoptosis in glioma cells. Furthermore, ZEB2 downregulation was accompanied by decreased expression of CDK4/6, Cyclin D1, Cyclin E, E2F1, and c-myc, while p15 and p21 were upregulated. Lowered expression of ZEB2 enhanced E-cadherin levels but also inhibited β-Catenin, Vimentin, N-cadherin, and Snail expression. Several apoptosis-related regulators such as Caspase-3, Caspase-6, Caspase-9, and Cleaved-PARP were activated while PARP was inhibited after ZEB2 siRNA treatment. Conclusion Overexpression of ZEB2 is an unfavorable factor that may facilitate glioma progression. Knockdown ZEB2 expression by siRNA suppressed cell proliferation, migration, invasion and promoted cell apoptosis in glioma cells.